Fractional statistics description applied to protein adsorption: effects of excluded surface area on adsorption equilibria - Quiroga, Evelina (2013)
Adsorption of large molecules blocking more than one adsorption center on a lattice is described as a fractional statistics problem, based on Haldane’s statistics. Excluded surface area is characterized by a statistical exclusion parameter, g, which relates to the molecular size and lattice geometry. The theoretical formalism reproduces the classical Langmuir equation (one excluded state limit), and gives a framework and compact equations to consistently describe the adsorption thermodynamics of structurally diverse proteins ranging from simple species to large ligands.